Height, weight and body mass index (BMI) in psychiatrically ill US Armed Forces personnel - WYATT, R. J. (Psychol Med, 2003)
BACKGROUND: In both psychiatrically ill and psychiatrically healthy adults, the connection between health and individuals’ height and weight has long been examined. Specifically, research on the idea that individuals with certain body types were prone to particular psychiatric diseases has been explored sporadically for centuries. The hypothesis that psychiatrically ill individuals were shorter and weighed less than psychiatrically healthy counterparts would correspond with the neurodevelopmental model of psychiatric disease. METHOD: To evaluate possible links between psychiatric illness and physique, the height, weight and BMI of 7514 patients and 85 940 controls were compared. All subjects were part of the National Collaborative Study of Early Psychosis and Suicide (NCSEPS). Patients were US military active duty personnel hospitalized for either bipolar disorder, major depressive disorder, or schizophrenia and controls were psychiatrically-healthy US military active duty personnel matched for date of entry into the service. RESULTS: No consistent differences in height, weight or BMI were found between patients and controls, or between patient groups. Some weak ANOVA differences were found between age at the time of entering active duty and weight, as well as BMI, but not height. CONCLUSIONS: Unlike most previous studies that have looked at the links between height and psychiatric illness, this study of the NCSEPS cohort found that, at entry into the US Armed Forces, there were no consistent decreases in height for patients with bipolar disorder, major depressive disorder or schizophrenia compared with a large control group. Furthermore, there were no consistent differences for weight or BMI.